Peran Lingkungan Kerja dan Fasilitas dalam Meningkatkan Motivasi dan Kinerja Karyawan - Nurudia, Maura (PRODUKTIF: Jurnal Kepegawaian dan Organisasi, 2024)
The work environment and facilities are two important factors that influence employee motivation and performance in an organization. Employees who work in a conducive environment and are equipped with adequate facilities tend to be more motivated and productive. The aim of this research is to measure the extent to which the work environment and facilities provided by the company can influence employee motivation and performance, as well as to provide strategic recommendations for improving the quality of the work environment and existing facilities. This research uses a quantitative approach with survey methods. Data was collected through questionnaires distributed to employees. The data analysis technique used is multiple linear regression to test the relationship between work environment variables, facilities, motivation and employee performance. The research results show that a conducive work environment and adequate facilities significantly influence employee motivation, which in turn has a positive impact on their performance. The work environment has a greater influence than facilities on employee motivation. In addition, motivation is proven to be a significant mediator between work environment and employee performance.